Primary Pharmacological and Other Important Findings on the Medicinal Plant "Aconitum Heterophyllum" (Aruna) - Debashish Paramanick; Ravindra Panday; Shiv Shankar Shukla; Vikash Sharma (Korean Pharmacopuncture Institute, 2017)
Abstract: Aconitum Heterophyllum (A. Heterophyllum) is an indigenous medicinal plant of India and belongs to the family Ranunculaceae. A. Heterophyllum is known to possess a number of therapeutic effects. For very ancient times, this plant has been used in some formulations in the traditional healing system of India, i.e., Ayurveda. It is reported to have use in treating patients with urinary infections, diarrhea, and inflammation. It also has been used as an expectorant and for the promotion of hepatoprotective activity. The chemical studies of the plant have revealed that various parts of the plant contain alkaloids, carbohydrates, proteins and amino acids, saponins, glycosides, quinones, flavonoids, terpenoids, etc. In the present study, a comprehensive phytochemistry and pharmacognosy, as well as the medicinal properties, of A. Heterophyllum are discussed. Abstract: Scientific information on the plant was collected from various sources,